Additional Diagnostic Value of Inversion Recovery Single-Shot Fast-Spin Echo Sequence in Differentiation Between Hepatic Hemangiomas and Cysts. Issue 4 (July 2015) - Atman, Ebru Düşünceli; Erden, Ayşe; Uzun, Çağlar; Yavuz, Yasemin
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to evaluate the additional diagnostic value of "inversion recovery" single-shot fast-spin echo (IR-SSFSE) sequence using the inversion time at the null point for hepatic hemangiomas as a supplement to standard T2-weighted (T2W) magnetic resonance imaging for the distinction of hemangiomas and cysts. Methods A total of 228 lesions in 56 patients were evaluated in this retrospective study. In addition to routine hepatic magnetic resonance imaging, IR-SSFSE imaging using inversion time value of 600 milliseconds (null point for hepatic hemangiomas) was obtained. Two radiologists independently reviewed T2W images at first and T2W images plus IR-SSFSE sequence 4 weeks afterward and used a 5-point scale to indicate the possibility of detected hyperintense lesion is a cyst or a hemangioma. A receiver operating characteristic analysis and κ statistics were used to evaluate the diagnostic additive value of IR-SSFSE sequence for differentiation of hepatic hemangiomas and cysts, and to determine interobserver agreement, respectively. Results Among 228 lesions, diameters of which ranges from 2 to 125 mm (mean, 13.84 ± 16.24 mm), 56.14% of them (n = 128) were hemangiomas, and 43.86% of them were cysts (n = 100). In the receiver operating characteristic analysis for the differentiation of hepatic hemangiomas from cysts, the calculated area under the curve (AUC) for standard T2W images alone was 0.889 (95% confidence interval [CI], 0.825–0.953) for the first observer and 0.913 (95% CI, 0.861–0.965) for the second observer. When IR-SSFSE sequence was combined to T2W images, AUC was calculated as 0.958 (95% CI, 0.920–0.996) for the first observer and 0.980 (95% CI, 0.956–1.0) for the second observer. The AUC values obtained from standard T2W images and standard T2W plus IR-SSFSE images were significantly different for both observers (P < 0.01). Both observers demonstrate better performance in differentiating hemangiomas and cysts with a combination of IR-SSFSE sequence and T2W imaging than with T2W imaging alone. Adding IR-SSFSE sequence as a supplement to standard T2W images improved the sensitivity and the κ values. Conclusions Inversion recovery single-shot fast-spin echo sequence using the inversion time to null signal from the hepatic hemangiomas as a supplement to standard T2W images is useful for distinguishing hemangiomas from hepatic cysts without the need for intravenous gadolinium chelate administration.